Anti-Photoaging Effects of Moisturizer and Serum Containing Andrographis paniculata, Syzygium aromaticum, and Pogostemon cablin: A Network Pharmacology, Molecular Docking, and in vivo Study - Adianingsih, Oktavia Rahayu; Johan, Christopher Kuncoro; Widarson; Ravsanjani, Eurica Andriani Najwa; Sutiyono, Bershiella Amandari; Qurrotuain, Iffah; Yurina, Valentina; Puspita, Oktavia Eka; Widasmara, Dhelya; Saitama, Akbar; Hariyono, Didik (Science and Technology Indonesia, 2026)
Ultraviolet-B (UVB)-induced photoaging accelerates collagen degradation, disrupts dermal structure, and compromises epidermal integrity. Natural extracts, such as Andrographis paniculata, Syzygium aromaticum, and Pogostemon cablin demonstrated antioxidant and anti-aging properties to mitigate these damages. This study investigated the protective effects of serum and moisturizer containing A. paniculata extract, S. aromaticum oil, and P. cablin oil on UVB-induced photoaging rats, by integrating network pharmacology and in vivo experiment. Compounds and photoaging-associated targets were retrieved through online databases. Enrichment analyses were performed using Metascape. Protein-protein interaction (PPI) construction and herbs-compounds-targets-pathways disease network were performed using STRING and Cytoscape 3.10.0, respectively, followed by molecular docking. An in vivo study was conducted to evaluate epidermal thickness, collagen density, and dermo-epidermal junction (DEJ) structure. Eleven key phytoconstituents and twelve core targets were identified in anti-photoaging molecular mechanisms using network pharmacology. Molecular docking analysis revealed that 7-O-methylwogonin demonstrated favorable binding against ten photoaging-associated targets. KEGG enrichment analysis showed potential inflammation processes inhibition, including photocarcinogenesis, AGE-RAGE signaling pathway, and TNF-α expression. Furthermore, treatment with serum, moisturizer, or combination of both significantly reduced epidermal thickening and enhanced collagen density compared to the UVB-exposed only group. Although no significant difference was observed in DEJ interdigitation index across groups, treated groups exhibited a trend towards better preservation of DEJ structure relative to the UVB group. In summary, serum and moisturizer containing A. paniculata, S. aromaticum, and P. cablin extracts demonstrated potential anti-photoaging effects by reducing epidermal thickness and preserving collagen density in UVB-exposed rats. These findings support these botanical-based formulations potential as effective anti-aging skincare.